Implementasi Program ASWAJA (Ahlusunnah Wal Jama’ah) dalam Meningkatkan Karakter Religius Siswa Sekolah Dasar - Dwinata, Anggara; Rachmadyanti, Putri; Siswanto, M Bambang Edi; Raharja, Hawwin Fitra; Nuruddin, Muhammad; Kibtiyah, Asriana (Universitas Nusantara PGRI Kediri, 2025)
ASWAJA (Ahlusunnah Wal Jama'ah) is a belief of the Nahdlatul Ulama (NU) with the characteristic of prioritizing three main teachings of Islam, namely understanding fiqh, aqidah, and tasawuf. In the context of education, ASWAJA is a program to improve religious character in students. The ASWAJA program is one of the interesting programs to be implemented in elementary school students so that students become a generation that is Qur'anic and has good morals. The aim of the research is to describe the ASWAJA program in improving the religious character of elementary school students comprehensively. This research was conducted at SD Islam Al Huda, Kediri City as one of the schools implementing the ASWAJA program. The research method used is a qualitative study with a case study design. Based on the results of the research that has been carried out, it is known that the ASWAJA program is very relevant in instilling religious character values ​​in students. This can be shown through activities in the ASWAJA program which are based on the principles of tasamuh (tolerance), i'tidal (perpendicular), and tawazun (maintaining balance). These three principles have a concretization of very implementative religious activities that are routinely carried out in daily, weekly, monthly, and yearly activities. So it can be concluded that the ASWAJA program is very suitable to be implemented in elementary schools in building students' religious character.